Chemical Composition Of Neem Seedlings (Azadirachta Indica L.) Sprayed With Arginine, Kinetin, And Chelated Iron - Mohammed, Nawras K.; Abdullah, Kadum M.; Fleih, Sabah A. (South Eastern European Journal of Public Health, 2024)
A pot experiment was carried out in the canopy of the Horticulture and Landscape Department - College of Agriculture - University of Kerbala during the 2023-2024 season to study the effect of kinetin (K) (0, 50, 100 mg L-1), arginine (A) (0, 150, 300 mg L-1), and chelated iron (F) (0 and 200 mg L-1) on some qualitative characteristics of neem seedlings. The study was implemented as a factorial experiment with a completely randomized block design with three replications. The majority of chemical features were significantly impacted by kinetin spraying, with the exception of the proportion of nitrogen, potassium, and protein in the leaves. Arginine affected all traits except total chlorophyll, while chelated iron mainly impacted potassium percentage. The research factors had varying effects on the features under investigation in the binary interaction findings. Treatment K1A1 produced the greatest rate of total chlorophyll, measuring 56.19 mg g-1 fresh weight, While the Fe2A2 treatment was superior in increasing the percentage of carbohydrates (13.31 mg g dry weight-1). With an average percentage of 3.308% for nitrogen content and 0.1588% for phosphorus, treatment K0A2 and treatment K1A2 respectively yielded the greatest percentages. However, treatment K0A1 produced a substantially higher percentage of protein, at 20.67%. Only the percentage of phosphorus was significantly affected by the triple intervention; the K1A0Fe2 treatment produced the highest rate of 0.1640%. This study concludes that High kinetin levels may have adverse effects, but when combined with nutrient-rich fertilizers, they can enhance seedling characteristics of trees with medicinal benefits.